IMPLEMENTATION OF QANUN NUMBER 11 OF 2018 CONCERNING ISLAMIC FINANCIAL INSTITUTIONS AT STATE-OWNED BANKS IN LHOKSEUMAWE CITY - Kamaly, Nurul; Bahri, M Irvanni (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2021)
This study will look into how regional regulation in Aceh is applied, specifically Qanun No.11 Year 2018 in terms of shari'a financial affiliate. This study is conducted at Bank Negara Indonesia (BNI), Bank Tabungan Negara (BTN), and Bank Mandiri, all of which are state-owned enterprises (BUMN) in the city of Lhokseumawe. This study's goal is to examine Qanun adoption by the aforementioned conventional banks, as well as the forecasts that those affiliates face in the process of implementing the Qanun of shari'a financial affiliate. This study is qualitative in nature since it completely and comprehensively explains the phenomena under investigation. Data was gathered by observation, interview, and documentation. The interactive model of inquiry was used to assess all of the data collected. According to the findings of this study, traditional banks have been devoted to Qanun implementation since 2019, starting with survey management and piloting public education linked to shari'a financial affiliate qanun. Traditional banks are currently in a 'ongoing' phase when it comes to the conversion of traditional accounts to shari'a accounts. Furthermore, asset asymmetry and employment management efforts have been ongoing. Nonetheless, there were a slew of roadblocks in the actual world. Among these were the growing lines of everyday customers wishing to convert their accounts to shari'a, the frequent occurrence of issues in the shari'a IT system, and the lack of clarity on the status of employees converting to shari'a. However, by 2021, every conventional bank in Aceh will have to be converted to shari'a law in accordance with Qanun No.11 of 2018.